Systematic Literature Review of the Development of Financial Information Systems in Churches - Wicaksono, Sherif Aji; Wijaksana, Candra Putra; Ngaeni, Nurus Sarifatul; Utami, Ema (International Journal of Computer and Information System (IJCIS), 2023)
This study was conducted to investigate the factors that influence the development of financial information systems in churches. The study used a systematic literature review with 10 studies that met the inclusion criteria. The findings of this study suggest that user involvement, technology selection, and change management are all important factors that influence the successful development of financial information systems in churches. Churches that are considering developing a financial information system should pay attention to these factors to increase their chances of success.Keywords : Financial information systems.